How is Logical Analysis Viable? - Arman Besler (Felsefe Dünyası)
The idea and the actual exercises of logical analysis as a philosophical method are at the heart of the emergence of analytic philosophy in the beginning of the 20th century. Although analytic philosophy is most commonly said to emerge with the critique devised by G. E. Moore and Bertrand Russell of the then-dominant idealist currents of philosophy in Britain, the central conception of analysis at work in this process is not the dominant traditional conception of analysis as decomposition of concepts, but a fairly new, distinctive conception which we find to be exemplified exclusively in Frege’s and Russell’s works (specifically Frege 1879, 1893 and Russell 1905). This distincive conception has been specified under a few various rubrics, such as paraphrastic or transformative-interpretive analysis, to separate it not only from the decompositional but the regressive conception as well, the latter characterizing the analysis-synthesis method of ancient Greek geometry. The present paper first locates logical analysis (as a philosophical method) in this picture, by proposing to define it as a definite kind of paraphrastic (or transformative/interpretive) analysis, the kind where the language in the analysans position is a logical language. The paper highlights the fact that the whole point of analyzing natural language forms by means of translating them into a logical language is essentially solving problems of inference – i.e. determining whether certain natural language sentence types follow from/contradict with/entail certain others, and shows that this particular conception of analysis is not as self-consistent a notion as it may first seem to be. The key to the argument is the undeniable connection between the meaning (at large) of a sentence form and the principal inferential relations that the sentence form is supposed (pre-analytically) to enter into with other related forms. The argument employs as a clear example the common modern logical analysis of the so-called problem of existential import of traditional categorical forms in order to problematize the viability of logical analysis, and concludes that one of the necessary conditions of the self-consistency (viability, possibility) of logical analysis is the acceptance of a certain negative thesis about meaning.